Use of Credit Cards as a Means of Payment in Trade Transactions at PT Bank Central Asia Tbk and PT Bank Danamon Indonesia Tbk Tangerang Branch - Tjandraningsih, Dewi (The International Journal of Law Review and State Administration, 2024)
This study aims to examine how to address misuse involving fraud, forgery, and theft related to credit card usage and explore methods for mitigating such issues. Additionally, the study investigates the legal protections available to parties involved in credit card transactions as a payment tool in commercial transactions. The research employs a normative legal approach, which involves examining problems based on legal principles, legal norms, applicable regulations, and relevant legal theories to provide a framework for verifying or testing truths. Conclusion Misuse can occur either by parties involved in the credit card mechanism or by third parties. Forms of misuse include: a. The issuer's failure to pay the merchant after a transaction between the cardholder and the merchant is completed. b. Various criminal activities, such as: 1) Forgery this includes the creation of counterfeit credit cards, forging authorized signatures, falsifying transactions, or duplicating cards. The primary goal of such criminal acts is personal gain or benefiting a syndicate targeting the issuing bank, which can indirectly harm legitimate cardholders and merchants.